Improvement of Bioactivity with Nanoparticle Fabrication: Cytotoxic Test of Ethanol, N-Hexane and Ethyl Acetate Extract from Red Galangal Rhizome (Alpinia purpurata (Vieill.) K. Schum) in Bulk and Nanoparticle size using BSLT Method - Enny Fachriyah; Dewi Kusrini; Pratama Jujur Wibawa (Jurnal Kimia Sains dan Aplikasi, 2018)
Some of the secondary metabolites present in red algae are terpenoids, quinones, flavonoids, alkaloids, essential oils, diarylheptanoids, steroids, cardioglycosides, oils and fats, tannins, carbohydrates. Activity of rhizomes, leaves and flowers red leaf is as antimicrobial, anti-fungal, anti-oxidants, anti-tumor, anti-cancer and vasodilator. One way to improve the physical, chemical and bioactivity properties of natural compounds was to make them into nanoparticles. In this study, the isolation of bioactive compounds contained in red laos rhizome by maceration method using ethanol solvent was done, then partitioned with n-hexane and ethyl acetate. The extracts thus obtained are fabricated into nanoparticles. Extracts in bulk and nanoparticles were then tested for cytotoxic activity using BSLT method. Results of analysis with PSA showed that ethanol extract had size 410,8 nm, n-hexane extract 220,7 nm and ethyl acetate extract 208,3 nm. The results of cytotoxic tests showed that nanoparticle size increased cytotoxic activity. Ethyl acetate extract was most active compared to ethanol and n-hexane extracts with LC50values of 17.919; 84,956; 166,526 ppm. Whereas the nanoparticle size was respectively 10,491; 74,072 and 84,197 ppm. Cytotoxic activity increases with nanoparticle fabrication.